Rapid Response of Biologic Treatments of Moderate-to-Severe Plaque Psoriasis: A Comprehensive Investigation Using Bayesian and Frequentist Network Meta-analyses - Richard B. Warren; Kyoungah See; Russel Burge; Ying Zhang; Alan Brnabic; Gaia Gallo; Alyssa Garrelts; Alexander Egeberg (Adis, Springer Healthcare, 2019)
Abstract Introduction Rapid improvement of psoriasis is valued by patients and should be considered to be an important factor in treatment selection. We investigated Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) response rates within the first 12 weeks of treatment to compare the rapid response of 11 biologic therapies for moderate-to-severe psoriasis using Bayesian and Frequentist network meta-analyses (NMA). Methods A systematic literature review was conducted to identify phase 3, double-blind, randomized, controlled trials for adult patients with moderate-to-severe psoriasis treated with interleukin (IL)-17 (brodalumab, ixekizumab, secukinumab), IL-12/-23 (ustekinumab), IL-23 (guselkumab, risankizumab, tildrakizumab), or tumor necrosis factor inhibitors (adalimumab, certolizumab pegol, etanercept, infliximab). Outcome measures extracted from 32 publications were ≥ 75, ≥ 90, or 100% improvement in PASI score (PASI  75, PASI 90, or PASI 100, respectively) at weeks 2, 4, 8, and 12 and DLQI    (0,1), where score (0,1) indicates no effect on patient's life, at week 12. Bayesian NMA (BNMA) used fixed-treatment effect and random-baseline effect, normal independent models. Frequentist NMA (fNMA) was conducted as sensitivity analyses to test the robustness of the findings. Results Based on BNMA and fNMA, brodalumab and ixekizumab showed the most rapid treatment effects on PASI 75 at weeks 2, 4, and 8 and on PASI 90 and PASI 100 at weeks 2, 4, 8, and 12; ixekizumab overlapped with risankizumab on PASI 75 at week 12. Brodalumab, ixekizumab, and secukinumab yielded higher DLQI (0,1) gains at week 12 compared to all of the other biologics studied. Additional measures of quality of life were not assessed in this report. Conclusions Ixekizumab and brodalumab provide the most rapid response and earliest clinical benefit at week 2 among all of the biologics studied, including other biologic treatments such as secukinumab, ustekinumab, guselkumab, adalimumab, and etanercept. BNMA and fNMA results showed similar relative effect estimates and treatment rankings. Funding Eli Lilly and Company.